Breaking Silo Thinking within the South African Water-Energy-Food Nexus via Systems Thinking and Simulation Workshops - Steven Mathetsa; Corne du Plooy; Khabeer Tayob (Journal of Digital Food, Energy & Water Systems)
Despite their inextricable interlinkage commonly known as Water-Energy-Food nexus, the current disconnect in policy development and management of the water, energy, and food resources threatens their security of supply. The security of these basic human needs is aggravated by the cross-cutting role of climate change which impacts their availability.  These apprehensions suggest that contemporary methods are required to improve and enhance integrated approaches and systems in the management of the food, water, and energy sectors within the discourse of climate change. This study applied Systems Thinking methodologies to foster collaboration amongst key stakeholders within Eskom, electricity generating sector in South Africa. This was done through several simulation workshops held amongst these value chain sectors. The workshops have demonstrated the ability of these systems to enable stakeholders to apply the “nexus thinking” approach in managing the sectors of water, food, energy, and climate change within the power utility. The study concluded by recommending application of this simulation within the policy development and other key sectors to enable a broader application of nexus thinking.